Modelo ProLab: Salud Mental al Alcance de Todos, una iniciativa digital para el cuidado de la salud mental en Perú - Chavez Alegria, Karem Stacy (2025)
The project addresses the problem of inequality in access to mental health services in a world where the pressure and demand for immediate results are increasing, access to resources for the management of emotional health has become essential, especially for young adults in urban environments. An innovative solution is presented: the "Masimente" mobile application. This platform is designed to destigmatize, educate and raise awareness about emotional health, offering practical tools for managing emotions. with the purpose of promoting the emotional and physical well-being of young adults, regardless of their location or available resources. The core of the proposal is an intelligent virtual pet that acts as an emotional support companion. Through daily interaction with the pet, users can express their emotions, receive personalized advice and, if necessary, be referred to mental health professionals. In addition, it includes games and challenges that promote emotional well-being, a gratitude journal to reflect on the positive, and options to personalize the pet. Masimente's impact is expected to be considerable as it addresses the gap in access to mental health for young people. By promoting self-management and emotional awareness, the app has the potential to reduce the burden on healthcare systems and significantly improve users' quality of life. In short, Masimente offers a practical and scalable solution to a pressing social problem, with the potential to positively transform the lives of millions of young adults in urban environments.